RIGID UNIT MODES AT HIGH PRESSURE: AN EXPLORATIVE STUDY OF A FIBROUS ZEOLITE-LIKE FRAMEWORK WITH EDI TOPOLOGY - Gatta G.D.; Wells S.A. (My University, 2004)
We report a comparative study on the high pressure (HP) structural behaviour of a fibrous zeolite (with EDI topology) on the basis of rigid unit modes (RUM) modelling and previously published single-crystal X-ray diffraction. HP single-crystal diffraction data lead to a more precise determination of the elastic parameters (axial and volume compressibilities) useful to define the equation-of-state under isothermal conditions, and the structural refinements are useful to describe the main deformation mechanisms of the Si/Al framework and extra-framework content at high pressure. The RUM modelling is applied to simulate the compressive behaviour of the framework, under hydrostatic and non-hydrostatic conditions, using a minimum number of parameters, and to describe the deformation mechanism intuitively in terms of the rotations of the SiO4 polyhedra. The local and global P-induced deformation mechanisms of the Si/Al framework observed in experiment (channel ellipticity, SBU rotation) are well reproduced by RUM modelling. The simulation of uniaxial compression (non-hydrostatic conditions) shows an interesting result on the structural behaviour. This comparative study tests the reliability of the RUM modelling in open-framework silicates with a complicated crystal structure.
Keywords: Fibrous zeolite; Edingtonite; High pressure single-crystal X-ray diffraction; Rigid unit modes